PERILAKU ORGANISASI GURU DALAM MENINGKATKAN MUTU PEMBELAJARAN: SEBUAH PENELITIAN NARATIF DI SEKOLAH DASAR - Ai Dina Saadiah; Siti Maesyaroh; Cucu Atikah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abstrak This study aims to describe teachers’ organizational behavior in improving the quality of learning in elementary schools. The research used a qualitative approach with a narrative inquiry design. Data were collected through in-depth interviews, observations, and reflections on teachers’ real experiences in a supervisor’s assisted school. The results show that teachers’ organizational behavior characterized by collaboration, open communication, and professional commitment plays a vital role in creating a quality learning environment. Furthermore, values of togetherness, trust, and participatory leadership of the principal strengthen the organizational culture that supports quality learning. This study affirms that improving learning quality depends not only on curriculum innovation but also on healthy, learning-oriented organizational behavior.